Utilizing the e-Government Framework as Principles for the Development of Digital Libraries and Archives - Kamar, Nerisa; Otenyo, S.C. (My University, 2010)
Information Communication Technologies (ICTs) have been embraced in most developing countries as a vehicle to provide government information and documents through the e-government concept. This paper attempts to give highlights of Kenya’s 2006 ICT strategy, Strategic Plan (2004), e-Government Strategy (2004), ICT Investor Guide, Draft Freedom of Information Bill (April 2007), Freedom of Information Policy (April 2007) and e-Transaction Bill 2007, and how these can guide the development of digital libraries and archives. It concludes by discussing hindering factors and challenges in the development of digital libraries and archives. These include infrastructure, finance, copyright and human resources, and gives highlights on the way forward and recommendations.
Keywords: ICADLA, conference, digital library, archive, Africa, Kenya, e-government